Intraspecific classification of durum wheat: new botanical varieties and forms - O. A. Lyapunova (Вавиловский журнал генетики и селекции)
The Wheat Genetic Resources Department of VIR treats Triticum durum Desf. as a separate species. It contains 2 subspecies: subsp. durum and subsp. horanicum. Subsp. horanicum Vav. shows the highest spike density. Subsp. durum – the durum wheat proper – is characterized by a major variation of spike density, grain size and form. The subspecies also has liguleless forms and those with strongly pubescent leaves. The subsp. durum is represented by 6 groups of botanical varieties (convarieties): durum, durocompactum, aglossicon, villosum, falcatum, and caucasicum. Convar. durum has three subconvarieties: durum, muticum and duroramosum. At the time of the development of the classification 121 botanical varieties were described within T. durum. They were identified by a combination of characteristics such as the presence or absence of pubescent straw under the spike, pubescent or glabrous glumes, the roughness of awns (smooth or rough), glume color (white, red, gray, smoked-grayish or black on white or red background), awn color (same color as that of glumes or black), kernel color (white, red or purple). The principle of selection of botanical varieties is based on the combination of a large number of signs, giving a large number of possible options. It is very likely that most of them are not found in nature, but the probability of finding a new botanical variety or the presence of various forms can be increased as the research of polymorphism in accessions of the durum wheat collection in different ecological and geographical conditions. The objects of research were about 6000 accessions from the VIR durum wheat genetic collection, which had been grown in different ecological and geographical conditions during for 15 years. Identification of the accessions was carried out in accordance with the classification used by the Wheat GR department in its work with the collection. As a result of their own field research in ICARDA (Syria, Tel Hadya) and identification of accessions obtained after reproduction on the VIR experimental station, we have identified 10 new botanical varieties and 12 forms of T. durum to supplement the classification. For each of them the diagnosis is given, the type is defined, a herbarium (autotype) and photos are provided.